Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1200/jco.1992.10.3.364
|View full text |Cite
|
Sign up to set email alerts
|

2-Chlorodeoxyadenosine produces a high rate of complete hematologic remission in relapsed acute myeloid leukemia.

Abstract: 2-CDA given by prolonged continuous infusion has clinically significant activity against AML and merits further testing in multidrug regimens for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(67 citation statements)
references
References 11 publications
3
63
0
Order By: Relevance
“…3 For pediatric patients, it is known that intensive second-line treatment induces remission in a proportion of patients and at least some of the children may have a chance of cure. 4,5 In reports on experimental therapies evaluating drugs in phase II studies [6][7][8] patient numbers are usually small and long-term follow-up is rarely reported. Therefore no conclusions for the prognosis of children with relapsed AML can be drawn.…”
Section: Introductionmentioning
confidence: 99%
“…3 For pediatric patients, it is known that intensive second-line treatment induces remission in a proportion of patients and at least some of the children may have a chance of cure. 4,5 In reports on experimental therapies evaluating drugs in phase II studies [6][7][8] patient numbers are usually small and long-term follow-up is rarely reported. Therefore no conclusions for the prognosis of children with relapsed AML can be drawn.…”
Section: Introductionmentioning
confidence: 99%
“…The most impressive responses have been observed in patients with hairy-cell leukemia, in whom complete response rates of 90% with prolonged remission can be achieved [23,24]. In children, the use of 2-CdA has been restricted almost exclusively to the treatment of acute myeloid leukemia, where a response rate of 59% has been documented [25]. Based on preclinical data that showed that the killing of lymphocytes in culture is time-dependent [26], a continuous infusion schedule over 5À7 days was used in early clinical trials [18,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with other salvage regimens in AML, infectious mortality (7/30) is similar 12,30 or superior. 17,[31][32][33] Nephrotoxicity is a serious cause of concern when using CBDCA. In order to avoid this problem, some authors 34 have recently recommended that the CBDCA dosage be based on renal function with promising results.…”
Section: Discussionmentioning
confidence: 99%